A Compendium of Research Addressing Barriers to Student Recruitment and Retention in Vocational Education in Florida. Final Report from September 1, 1984 to December 31, 1984 Freddie C. Waltz and Carl E. Beeman. - Waltz, Freddie C. (Distributed by ERIC Clearinghouse, 1984)
To address the issues of student recruitment and retention in Florida, a three-year research study was conducted. The three phases of the study sought the following: (1) to describe barriers to recruitment and retention of disadvantaged, unemployed, underemployed, out-of-school youth as perceived by students, teachers, counselors, and administrators; (2) to develop a means for implementing proven recruitment strategies to attract and retain students in postsecondary vocational programs; and (3) to identify factors that influenced students who were currently enrolled in a postsecondary vocational program to enroll and also the factors that influenced them to continue enrollment. Data were gathered through interviews and by mail surveys of students, teachers, counselors, and administrators. Results of data analysis showed that administrators, teachers, and counselors relied too often on recruitment strategies that were less successful, such as booths at fairs, and that students and professional personnel perceived different strategies as most effective. For example, school officials thought that "personal contact with students enrolled in the program or program graduates" was the most effective strategy, while students rated it fairly low. The study produced a recruitment manual that school personnel could use to enhance their chances of successful recruitment and retention of disadvantaged students. (KC)